Unravelling the Export-Employment Nexus: Empirical Evidence from the Organization of Turkic States - ZEYNALLI, Latif; RUSTAMOV, Ilham; ABASOV, Elchin; HASANOGLU, Murteza (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025DO - 10.14505/tpref.v16.2(34).08, 2025)
This study explores the complex relationship between export dynamics and employment trends in the member states of the Organization of Turkic States (OTS). While existing literature presents varying findings on this relationship, this research utilizes panel data analysis covering the period from 2000 to 2023 to provide empirical insights. By employing employment and export data, the study applies the Hausman test to identify the most appropriate econometric model, ultimately opting for the Random Effects Model for estimation. The empirical findings indicate a positive and statistically significant relationship between export growth and employment expansion. Specifically, a 1% increase in exports is linked to a corresponding rise in employment levels, supporting the hypothesis that trade activities contribute to improvements in the labor market within OTS economies. However, the magnitude of this effect varies based on sectoral differences and macroeconomic conditions.  The results highlight the critical importance of export-oriented policies in promoting employment opportunities while emphasizing the need for structural reforms to address potential imbalances in the labor market. This study adds to the broader discussion on trade and employment by providing policy recommendations for OTS countries to enhance their economic strategies.